Case report: Clinical and neuroradiological longitudinal follow-up in Leukoencephalopathy with Calcifications and Cysts during treatment with bevacizumab - Scaffei, Elena; Buchignani, Bianca; Pasquariello, Rosa; Cristofani, Paola; Canapicchi, Raffaello; Biagi, Laura; Giordano, Flavio; De Marco, Emanuela; Crow, Yanick J.; Battini, Roberta (Frontiers in Neurology, 2023)
Leukoencephalopathy with Calcifications and Cysts (LCC) is a rare genetic microangiopathy exclusively affecting the central nervous system caused by biallelic mutations in SNORD118. Brain magnetic resonance imaging (MRI) is often diagnostic due to the highly characteristic triad of leukoencephalopathy, intracranial calcifications, and brain cysts. Age at onset, presentation and disease evolution can all vary, ranging from pauci-symptomatic disease to rapid evolution of signs with loss of motor and cognitive abilities. No specific therapies for LCC are currently licensed.According to the literature, bevacizumab might represent an effective modality to improve the clinical and MRI features of the disease. However, uncertainty remains as to the true efficacy of this approach, when to begin therapy, appropriate dosing, and the consequences of drug withdrawal.According to CARE guidelines, we describe the long-term clinical and neuro-radiological followup of a 10-year-old child with LCC. We report disease evolution following repeated cycles of treatment with bevacizumab. Our case report suggests that repeated cycles of bevacizumab might effectively modify disease progression, possibly indicating a time-dependent effect.